Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1460-9568.2009.06729.x
|View full text |Cite
|
Sign up to set email alerts
|

The dorsal premotor cortex orchestrates concurrent speech and fingertapping movements

Abstract: Human speech and hand use both involve highly specialized complex movement patterns. Whereas previous studies in detail characterized the cortical motor systems mediating speech and finger movements, the network that provides coordination of concurrent speech and hand movements so far is unknown. Using functional magnetic resonance imaging (fMRI), the present study investigated differential cortical networks devoted to speech or fingertapping, and regions mediating integration of these complex movement pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…There are a few studies that investigated the effector-independent activations related to rhythm tapping [6,7,8]. The study by Meister et al reported brain activations during tapping or articulation at a constant rate, and that by Bengtsson et al described activations during synchronization and reproduction of well-trained rhythmic sequences.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few studies that investigated the effector-independent activations related to rhythm tapping [6,7,8]. The study by Meister et al reported brain activations during tapping or articulation at a constant rate, and that by Bengtsson et al described activations during synchronization and reproduction of well-trained rhythmic sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Their function has been interpreted in terms of goaldirected planning, planning of hand movements, and adequate sequencing of motor commands respectively (Buxbaum et al, 2006;Davare et al, 2010;Grafton et al, 1998;Lewis, 2006;Makuuchi et al, 2012;Meister et al, 2009;Vingerhoets et al, 2013). The focus of vPMC of matching hand posture configurations in accordance to visual demands is nicely demonstrated by its close correspondence with inferior parietal and extrastriate regions, whereas the focus of DLPFC and dPMC on the planning of motor control is underlined by its strong reciprocal connections (see Figure 4B).…”
Section: Frontal Regionsmentioning
confidence: 99%
“…As part of the dorsal route for speech perception proposed by Hickok and Poeppel (2007), overlapping representations of the manual and speech articulators (e.g. Meister, Buelte, Staedtgen, Boroojerdi, & Sparing, 2009) may enable dorsal premotor cortex to participate in audiovisual and sensorimotor integration (Josse et al 2012). For example, premotor cortex, along with the planum temporale and STG, are thought to form a network that supports sensorimotor integration for error detection and correction by providing auditory feedback during speech production (Hickok, Houde, & Rong, 2011; Tourville, Reilly, & Guenther, 2008).…”
Section: Discussionmentioning
confidence: 99%